Switching spatial reference frames for yaw and pitch navigation - Gramann, Klaus; Wing, Shawn; Jung, Tzyy-Ping; Viirre, Erik; Riecke, Bernhard E. (Spatial Cognition and Computation, 2012)
Humans demonstrate preferences to use egocentric or allocentric reference frames in navigation tasks that lack embodied (vestibular and/or proprioceptive) cues. Here, we investigated how reference frame proclivities affect spatial navigation in horizontal versus vertical planes. Point-to-origin performance after visually displayed vertical trajectories was surprisingly accurate and almost matched yaw performance for both egocentric and allocentric strategies. For vertical direction changes, 39% of participants unexpectedly switched to their non-preferred (allocentric) reference frame. This might be explained by vertical (25°–90° up/downward pitched) trajectories having lower ecological validity and creating more pronounced visuo-vestibular conflicts, emphasizing individual differences in processing idiothetic, embodied sensory information. (PsycINFO Database Record (c) 2012 APA, all rights reserved) (journal abstract)
Keywords: Allocentrism; Cues; Egocentrism; Gravitational Effects; Pitch Perception; Riecke; Riecke_2012; Spatial Organization; embodied cues; journalPaper; klaus-gramann; pitch navigation; point-to-origin; proj--Gramann-PathInt; spatial reference frames; yaw navigation